Pengaruh Harga Dan Promosi Terhadap Keputusan Pembelian Dengan Citra Merek Sebagai Variabel Intervening (Studi Pada Kedai Pesen Kopi Di Kota Malang) - Mirza Rosnita; Agus Widarko; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe culture of drinking coffee in Indonesia has been developing for a long time, since the first time the forced cultivation system was initiated by the Dutch government, at first drinking coffee was a habit practiced by the Dutch government, along with its development the Indonesian people began to like to drink coffee.This study aims to determine the direct effect of price, promotion and brand image on purchasing decisions and brand image as an intervening variable. The population used in this study are people in Malang City who still subscribe to or who have visited the Pesen Kopi Shop in Malang City. The sampling method used was purposive sampling, which was taken with certain criteria, namely 107 respondents. Using path analysis, and the research results show that price and promotion have a direct effect on brand image, price has no effect on purchasing decisions, promotions have a direct effect on decisions and brand image variables are able to mediate prices and promotions on purchasing decisions. Keywords : price, promotion, brand image and purchase decision